ISOLATION AND EXAMINATION OF NAIL FUNGUS (ONYCHOMYCOSIS) IN THE NAILS OF FIELD FARMERS - Paramata, Nanang Roswita (Jambura Nursing Journal, 2024)
Onychomycosis is a superficial fungal infection, this fungus is found all over the world without exception in Gorontalo Province. The purpose of this research is to determine the type of fungus that causes onychomycosis. This research is a type of quantitative research with experimental methods using KOH (Potassium Hydroxide) and observing microscopically. The research population is farmers who work in the fields with a sample of 10 respondents using a total sampling technique and the data used is univariate data. The results found from 10 respondents, 5 respondents (50%) the results were positive and 5 respondents (50%) the results were negative. The fungi that cause onychomycosis are Tricophyton mentagrophytes and Epidermophyton floccosum. With this research, it is hoped that the type of fungus that causes infection in the nails can be identified. Also can be a reference for further research and information for the advancement of science and technology. Key Word : Onikomikosis, KOH